1990
DOI: 10.1152/jn.1990.63.5.1169
|View full text |Cite
|
Sign up to set email alerts
|

Recordings from cat trapezoid body and HRP labeling of globular bushy cell axons

Abstract: 1. Recordings were made from single nerve fibers in barbiturate-anesthetized cats in the midline trapezoid body, a location that permits selective sampling of efferent cells of the ventral cochlear nucleus. Single units were localized to either the dorsal or ventral components of the trapezoid body. The fibers were physiologically classified on the basis of their peristimulus time histograms (PSTH) and receptive-field properties. In addition, low characteristic frequency (CF) units were probed for rapid rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
168
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 0 publications
11
168
0
Order By: Relevance
“…Therefore, the frequency of occurrence of a high-frequency inhibitory effect is unknown, as is whether inhibitory inputs play a role over the entire frequency range. However, inhibition was reported in nearly all fibers with a PLn response that were recorded in the trapezoid body (Spirou et al, 1990).…”
Section: Receptive Fieldsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the frequency of occurrence of a high-frequency inhibitory effect is unknown, as is whether inhibitory inputs play a role over the entire frequency range. However, inhibition was reported in nearly all fibers with a PLn response that were recorded in the trapezoid body (Spirou et al, 1990).…”
Section: Receptive Fieldsmentioning
confidence: 99%
“…This was based on a scatter diagram comparing the spontaneous and maximum discharge rates of a relatively small number of PLn units, where clusters of points suggested that there could be 1-3 high-spon ANFs contacting the cell and that each ANF generated EPSPs which were above threshold (see discussion in Spirou et al, 1990). A comparison of the scatter diagram of maximum discharge rate versus SR for the population of GBCs in the present report showed that there are clusters of points, suggesting that individual endbulbs can discharge the postsynaptic element, i.e., all endbulbs are not created equal in terms of synaptic strength.…”
Section: Variety Of Psth Patternsmentioning
confidence: 99%
See 3 more Smart Citations